How to learn science in an enviromentally friendly inclusive school? - Ikhlasul Ardi Nugroho; Pradita Rizky Wirawan (Universitas Sebelas Maret, 2026)
Knowledge of good practices of science learning in inclusive and environmentally friendly schools is currently not well presented. This study aims to find patterns of planning activities, learning activities, and assessment patterns of science learning in environmentally friendly and inclusive schools. The research method used is an explanatory case study using Spradley analysis where the research subjects were determined through purposive sampling and consisted of the principal, class teachers, and special assistant teachers at Giwangan State Elementary School, Yogyakarta. Data collection techniques used interviews, observations, and documentation studies with the instruments used being interview guides, observation sheets, and document study sheets. The conclusions of this study are: (1) Learning planning begins with transformational leadership and comprehensive policies and collaborative planning; (2) Collaborative learning activities that realize physical, social, and teaching integration and train science process skills; and (3) learning assessment is carried out collaboratively and fulfills students' rights. The implications of this study are in the form of affirmation of ecological theory and the concept of deep ecology.